Retracted: How Do Renewable Energy, Economic Growth and Natural Resources Rent Affect Environmental Sustainability in a Globalized Economy? Evidence From Colombia Based on the Gradual Shift Causality Approach - Awosusi, Abraham Ayobamiji; Mata, Mário Nuno; Ahmed, Zahoor; Coelho, Manuel Francisco; Altuntaş, Mehmet; Martins, José Moleiro; Martins, Jéssica Nunes; Onifade, Stephen Taiwo (Frontiers in Energy Research, 2022)
Undoubtedly, fossil fuel energy consumption causes global warming. The question at the core is whether or not we want to quit energy consumption? The obvious answer to this question is “no.” Therefore, the necessity for innovation is curial to attain green energy and sustainable growth. This research specifically focused on Colombia, which represents the aforementioned threats to a large extent as the trajectory of economic expansion is characterized by significant CO2 emissions in Colombia. In this regard, we examine the association between globalization, renewable energy, natural resources rent, economic growth, and CO2 emissions from 1970 to 2017. The cointegration test confirmed a long association between the considered variables. This study employed the Fully Modified Ordinary Least Squares, Dynamic Ordinary Least Squares, and Autoregressive Distributed Lag estimators for the long-run analysis. The long-run empirical results uncovered growth-induced emissions in Colombia. The result illustrated that the path of development is unsustainable in Columbia. In contrast, globalization and renewable energy demonstrated a favorable contribution to environmental quality. The outcomes of the Gradual Shift Causality indicated that globalization, natural resource rent, and economic growth Granger cause CO2 emissions. The findings highlight the need to enact well-coordinated measures to reduce environmental deterioration in Colombia. Colombia must aggressively promote the development of renewable energy and also foster a better viable environment for renewable energy investment to mitigate environmental damage caused by economic growth.